"Implementasi Metode Multi-Sensori untuk Keterampilan Sosial dan Kemampuan Kognitif Anak Berkebutuhan Khusus di SLB Serasan Seandanan OKU Selatan" - UMMY; FARHAN; JUAIDAH (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to describe the implementation of the multi-sensory method to enhance the social skills and cognitive abilities of children with special needs at Serasan Seandanan Special School, South OKU. The problem arises from the need for appropriate learning approaches tailored to individual characteristics, especially for children who often face challenges in social interaction and cognitive development within inclusive education settings. The Data were collected through observation, in-depth interviews, and documentation involving teachers, the school principal, and students. The findings show that multi-sensory activities—incorporating visual, auditory, kinesthetic, and tactile stimuli—have a positive effect on students' social engagement, empathy, cooperation, and communication skills. Moreover, these methods also stimulate cognitive development through enjoyable, concrete learning experiences. The consistent and structured application of the multi-sensory method resulted in increased student participation and improvements in essential social and cognitive competencies. Keywords: Children with Special Needs, Cognitive Ability, Multi-Sensory Method, Social Skills, Special School (SLB).